Early Childhood Character Education In The Perspective Of Independent Curriculum - Nopiana Nopiana (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2025)
Early childhood character education is the main foundation in forming a good personality and integrity. The Independent Curriculum provides flexible space for educators to develop character-based learning according to the needs of students. This literature study aims to analyze the concept of early childhood character education from the perspective of the Independent Curriculum and its implications for educational practices in Indonesia. Using the literature study method, this study examines various academic sources related to the implementation of character education, the approaches used, and the challenges faced in its implementation. The results of the study show that the Independent Curriculum emphasizes child-centered learning, differentiation in learning, and character strengthening through project-based activities. Character education in this curriculum emphasizes moral, ethical, and social values ​​that are introduced contextually to children. In addition, the role of teachers and parents is a key factor in the successful implementation of character education. This study recommends intensive training for educators and policy support that strengthens character education from an early age.